Implementasi Undang Undang Nomor 22 Tahun 2022 Tentang Pemasyarakatan Terhadap Peningkatan Keterampilan Anak Binaan: (Studi Di Lembaga Pembinaan Khusus Anak Kelas II Batam) - Nursa Erizon; Muhamad Hasan Sebyar (Lembaga Pengembangan Kinerja Dosen, 2024)
Skills are a product of the fostered child development system for children in conflict with the law (ABH) and are an embodiment of justice with the aim of gaining social personality or restoring unity in the relationship between prisoners and society. Not only as a direction or goal of correctional crime, but also as a treatment of prisoners because educating children who are in conflict with the law (ABH) is not an effort or medium to take revenge or take revenge. Educational dimension development includes an understanding that the imposition of criminal sanctions can empower the social life of children who are in conflict with the law to have a healthy social personality. This research study is to ascertain how the coaching pattern is carried out in order to achieve an increase in the skills of the target children at the Batam Class II Batam Class II Special Development Institute for Children in accordance with Law Number 22 of 2022 concerning Corrections. Empirical legal studies are a type of research that is used by making observations in collecting data as well as using a literature study and documentation approach as support. Books, journal articles and other forms of scientific writing were used. The results of the study show that the implementation of the skills program in optimizing social independence for assisted children at the Batam Class II Special Development Institute for Children has been implemented optimally although it still requires improvement, while Internal and External Factors are obstacles. implementation of skills acceleration in LPKA Class II BATAM.